Mekanisme Pembubaran Partai Politik di Indonesia - Ramot H.P Limbong; I Gusti Bagus Suryawan; I Nyoman Sutama (Jurnal Preferensi Hukum, 2020)
Political parties as legal entities may be subject to criminal liability as they are seen from the characteristic of political parties in accordance with the characteristics of the legal entity. The dissolution of political parties becomes one of the legal issues governed by Indonesian legislation. The problem of this research is: 1) how is the Constitutional Court Authority in the dissolution of political parties in Indonesia? 2) How is the mechanism of dissolution of political parties? The type of research and approach problems used is normative legal research and statutory approaches. The source of the legal material used is the primary source of legal material and the source of secondary legal material. The technique of collecting legal materials is the technique of library study. The collected legal materials are processed and analyzed using legal arguments. The result of this research is the procedure of the dissolution of political parties in the Constitutional Court as follows: Application submission, application registration and trial schedule, preliminary examination, trial examination, meeting Judge, the verdict of the Constitutional Court. The result of the dissolution of political parties may result in external rights and obligations, due to elected positions, due to the status of managers and members and the consequences of internal rights and obligations.